Application and research of new energy-efficiency technology for liquid ring vacuum pump based on turbulent drag reduction theory. (February 2020) - Zhang, Yifan; Zhou, Fubao; Li, Jinshi; Kang, Jianhong; Zhang, Qiangqiang
Abstract: The liquid ring vacuum (LRV) pump is a gas-liquid rotodynamic machine which has been widely applied for over a century in areas of gas pumping. However, its high energy consumption and low efficiency has been a dramatic limitation not effectively solved by the structural optimization design. Based on an energy balance model, a novel energy-efficiency technology for the LRV pump is proposed, which uses a polymer drag-reducing xanthan gum (XG) solution as the working fluid to reduce wall friction and turbulent loss to improve the pump efficiency. The effect of XG concentration on the rheological properties of XG solution and the LRV pump performance was investigated experimentally. The results show the XG solution shows a shear thinning and viscoelastic behavior, and at an inlet pressure of 60 kPa, the LRV pump efficiency is 34.4% in pure water, but can be greatly improved to 43.2% at an optimum concentration of 4500 ppm, corresponding to a 21.4% energy saving rate (ESR). Further, the variation of ESR with time induced by mechanical degradation is well fitted with two empirical decay equations. This technology has been industrially applied to reduce energy waste of the LRV pump, and a net energy cost saving 19.07% is achieved. Highlights: A new energy-efficiency technology for the LRV pump is proposed. An optimum XG concentration corresponding to highest LRV pump efficiency is found. Mechanical stability of XG solution with time is evaluated in the LRV pump. A fully-closed LRV pump energy-efficiency system is first applied in coal mine.